EDUCATIONAL APPROACHES TO DEVELOPING DRIBBLING SKILLS: THE INFLUENCE OF COORDINATION AND TRAINING METHODS AT KARYA MUDA FOOTBALL SCHOOL - Halim, Abdul; Bakhtiar, Syahrial; Bafirman, Bafirman; Damrah, Damrah; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
Based on the poor dribbling abilities of SSB Karya Muda Tanjung Pinang pupils, this study was conducted. The following are the objectives of this study: (1) to compare dribbling skills trained with drill methods and small side games (SSG); (2) to compare dribbling skills with low and high coordination; (3) to compare coordination abilities with training methods; (4) to compare dribbling skills trained with drill methods and SSG; and (5) to compare dribbling skills trained with drill methods and SSG.The type of research used is quasi-experimental. Purposive sampling was used to choose the sample, which included 32 students between the ages of 9 and 12. Instruments used: dribbling test and KTK. Data were analyzed using a two-way analysis of variance (ANOVA) technique with a 2x2 factorial design. Research results: 1) There are differences in the dribbling technique abilities of students in the SSG and drill training strategy groups (p < 0.05). 2) There is a difference in the dribbling technique abilities of students in the high and low coordination groups (p < 0.05). 3) There is an interaction between training strategy and coordination (p < 0.05). 4) There are differences in the dribbling technical abilities of students in the SSG and drill strategy groups with high coordination (Qcount 15.99 < Qtable 3.85). 5) There are differences in the dribbling technical abilities of students who are given SSG and drill training strategies with coordination (Qcount 6.27 < Qtable 3.85). The study's findings show that, although having similar levels